Inhalation carcinogenicity of dichloromethane in rats and mice. (9th June 2014) - Aiso, Shigetoshi; Take, Makoto; Kasai, Tatsuya; Senoh, Hideki; Umeda, Yumi; Matsumoto, Michiharu; Fukushima, Shoji
Abstract: The carcinogenicity of inhaled dichloromethane (DCM) was examined by exposing groups of 50 F344/DuCrj rats and 50 Crj: BDF1 mice of both sexes to 0, 1000, 2000, or 4000 ppm (w/w) DCM-containing aerosol for 2 years. Inhalation of DCM resulted in increased incidences of subcutis fibromas, mammary gland fibroadenoma, and peritoneum mesotheliomas in male rats; mammary gland fibroadenomas in female rats; and bronchiolar–alveolar adenomas and carcinomas in the lung and hepatocellular adenomas and carcinomas in male and female mice. These results clearly indicate that inhaled DCM is carcinogenic in F344/DuCrj (SPF) rats and Crj: BDF1 (SPF) mice.